Programs of work of Oklahoma N.F.A. chapters - Jenkins, James Monroe, author; Schmidt, G. A., advisor; Howard, Carl G., committee member; Aspinwall, Lloyd E., committee member; Duffey, T. L., committee member (Colorado State University. Libraries, 1941)
To view the abstract, please see the full text of the document.
Keywords: New Farmers of America -- Oklahoma; African American farmers -- Oklahoma